Cover Feature: A Titanium Dioxide Supported Gold Nanoparticle Catalyst for the Selective N‐Formylation of Functionalized Amines with Carbon Dioxide and Hydrogen (ChemCatChem 19/2017). Issue 19 (10th October 2017) - Mitsudome, Takato; Urayama, Teppei; Fujita, Shu; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract : The Cover Feature shows the environmentally benign N‐formylation of various amines over a TiO2 ‐supported gold nanoparticle catalyst using CO2 as the carbonyl source under a H2 atmosphere. In their Communication, T. Mitsudome et al. demonstrate that the gold catalyst is highly selective in the formylation of amines bearing reducible functional groups, whereas functional groups such as olefins, halogens, carbonyls, carbamates and cyano moieties are left intact during the reaction under H2 atmosphere (>99% selectivity). The catalyst is reusable without any loss of activity or selectivity. The high selectivity is attributed to the cooperative catalysis between gold nanoparticles and TiO2 . More information can be found in the Communication by T. Mitsudome et al. onpage 3632 in Issue 19, 2017 (DOI:10.1002/cctc.201700726 ).